(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
This article is a series of reflections generated through research and practice of an Indian Object Theatre company from 2011-2023. It reflects from the standpoint of the Indian context while looking at the history, development and practices in other parts of the world.